PENGARUH KOMPETENSI, MOTIVASI DAN KOMPENSASI TERHADAP KINERJA APARATUR PEMERINTAH DESA DALAM PENGELOLAAN KEUANGAN DESA BERBASIS SISKEUDES DI KECAMATAN REMBOKEN KABUPATEN MINAHASA - Ranndy Sterry Kindangen; David P. E. Saerang; Novi Swandari Budiarso (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2022)
The performance of the Village Government apparatus can be interpreted as the result of work or the level of achievement of the goals and objectives of the Village Government agencies. One of the goals that must be achieved by the Village Government is the realization of transparent and accountable village financial management which can be pursued through the use of the Village Financial System (Siskeudes). The aim of this study was to analyze and prove the effect of competence, motivation and compensation on the performance of Village Government apparatus in SISKEUDES-based village financial management in Remboken District, Minahasa Regency. The research method used was quantitative while the design of the study was explanatory survey with cross sectional approach. The population in this study was all Village Government apparatus who had roles as Village Financial Management Authority Holders (PKPKD) and Village Financial Management Implementers (PPKD) who spread over 11 villages in Remboken District, Minahasa Regency. The sampling technique used was saturation sampling or census method which amounted to 73 respondents of the population were determined as the samples. The data were collected using questionnaires instrument. The analysis for hypothesis testing was carried out using multiple linear regression test at significance level of 5%. The regression test includes the F statistic test, t statistic test and the coefficient of determination test. The results of thet test indicated that competence, motivation and compensation, either partially or simultaneously had a significant effect on the performance of Village Government apparatus in SISKEUDES-based village financial management in Remboken District, Minahasa Regency. The results of this study can be used as a benchmark for Village Government Agencies in evaluating the performance of the apparatus. In addition, the results can also be used as a reference in the implementation of various programs and policies to improve the competence, motivation and compensation of the apparatus which will have an impact on performance improvement.